Powder injection molding of Ti-Al-W nano/micro bimodal powders: Structure, phase composition and oxidation kinetics - Krinitcyn, Maksim G.; Pervikov, Alexander V.; Kochuev, Dmitriy; Lerner, Marat I. (Metals)
Products from the materials of the Ti-Al system are difficult to manufacture. This often restricts the use of such materials despite their outstanding properties. Some of the promising methods for manufacturing products, which allows working with materials of the Ti-Al system, are powder injection molding (PIM) and material extrusion additive manufacturing (MEAM) technologies. In the present study, powder composites Ti-48Al-4W with different powder size distribution, obtained by the electric explosion of wire (EEW) method, were investigated. The powder was used in PIM technology to produce bulk samples. After polymer debinding, PIM samples were sintered in a vacuum and using hot isostatic pressing (HIP) at the same temperatures and isothermal holding times. The results show the influence of size distribution and sintering method on the structure, phase composition, mechanical properties and oxidation resistance of pre-sintered PIM samples. It is found that both the size distribution and sintering method affect the mechanical properties. The smaller the particle size of the powder in the material, the greater the resistance to oxidation of such samples.